How a thief stole your data over network - Andreas Bernhard; Kurniawan Hagi (International Journal of Applied Business and Information Systems, 2017)
Until now, lot of companies that already have data that is so large and the development of data is so quickly and with the plurality of data formats. Not only in units hundreds of Mega or Giga again but have reached the realm of Tera data countless. Besides the diversity of the data format itself, today not just formatted text but can be video or image as well as the format of other data. With the trend of data continues to grow, sometimes aspect of data security was often overlooked and even ignored.